Type 2 Diabetes as a Risk Factor for Dementia in Women Compared With Men: A Pooled Analysis of 2.3 Million People Comprising More Than 100,000 Cases of Dementia - Chatterjee, S.; Peters, S.; Woodward, M.; Arango, S.; Batty, G.; Beckett, N.; Beiser, A.; Borenstein, A.; Crane, P.; Haan, M.; Hassing, L.; Hayden, K.; et al. (2015)
OBJECTIVE: Type 2 diabetes confers a greater excess risk of cardiovascular disease in women than in men. Diabetes is also a risk factor for dementia, but whether the association is similar in women and men remains unknown. We performed a meta-analysis of unpublished data to estimate the sex-specific relationship between women and men with diabetes with incident dementia. RESEARCH DESIGN AND METHODS: A systematic search identified studies published prior to November 2014 that had reported on the prospective association between diabetes and dementia. Study authors contributed unpublished sex-specific relative risks (RRs) and 95% CIs on the association between diabetes and all dementia and its subtypes. Sex-specific RRs and the women-to-men ratio of RRs (RRRs) were pooled using random-effects meta-analyses. RESULTS: Study-level data from 14 studies, 2,310,330 individuals, and 102,174 dementia case patients were included. In multiple-adjusted analyses, diabetes was associated with a 60% increased risk of any dementia in both sexes (women: pooled RR 1.62 [95% CI 1.45-1.80]; men: pooled RR 1.58 [95% CI 1.38-1.81]). The diabetes-associated RRs for vascular dementia were 2.34 (95% CI 1.86-2.94) in women and 1.73 (95% CI 1.61-1.85) in men, and for nonvascular dementia the RRs were 1.53 (95% CI 1.35-1.73) in women and 1.49 (95% CI 1.31-1.69) in men. Overall, women with diabetes had a 19% greater risk for the development of vascular dementia than men (multiple-adjusted RRR 1.19 [95% CI 1.08-1.30]; P < 0.001). CONCLUSIONS: Individuals with type 2 diabetes are at ~60% greater risk for the development of dementia compared with those without diabetes. For vascular dementia, but not for nonvascular dementia, the additional risk is greater in women.